REGRESSION MODELING IN RICE PRODUCTION AND DOMESTIC REGIONAL BRUTO PRODUCTS LAMPUNG PROVINCE - Reni Permata Sari (Universitas Nahdlatul Ulama Lampung, 2019)
The agricultural sector is one sector that has an important role in the development of Lampung Province. Rice-specific food crops are a strategic commodity because they are the main foodstuff of the Indonesian people, and the Lampung community in particular. The need for an increase in the productivity of rice plants in Lampung is an important note for the Lampung Province government. One of the goals of agricultural development is to improve the welfare of farmers and improve food welfare. Considering rice commodity in supporting development in Lampung, it is necessary to study the relationship of rice production to the Gross Regional Domestic Product of the agricultural sector in Lampung Province. Results of research conducted on the Gross Regional Domestic Product of the agricultural sector in Lampung Province, namely: (1) Gross Regional Domestic Product of Lampung Province in the agriculture, agriculture, agriculture, and agriculture sectors related to a very strong positive linear relationship with the amount of production rice in Lampung Province, (2) The higher the amount of rice production in Lampung Province, the higher the Regional Gross Domestic Product of Lampung Province in the agriculture, animal husbandry, mining, and fishery sectors, and (3) Polynomial Model with a degree of Y = - 1521 + 185 x - 6.88 x2 + 0.0860 x3 with Y as the Gross Regional Domestic Product and X as the amount of rice production in Lampung Province is the best model that can explain the relationship between each.